Humor through Exploitation of Meaning Duality in English Memes - Widiatmika, Putu Wahyu; Segara, Ida Bagus Made Ari; Kusuma, Ni Made Yunita Widya (J-Lalite: Journal of English Studies, 2024)
There are many mechanisms to integrate humor in English memes. One common method is to make incongruity through two different interpretations. The incongruity can be implemented on different levels, such as lexical, syntactic, and more. However, not everyone can understand these levels; thus, the delivery of humor is not achievable. Therefore, this study aims to analyze meaning duality causing humor in English memes. There were 30 data collected from Pinterest through documentation method. The analysis was conducted with content analysis method through descriptive-mixed approach based on theories of incongruity, ambiguity, context of situation, and generative transformation. The result shows that all types of ambiguity is found and can create meaning duality that causes humor from incongruous finishing text. Lexical ambiguity is the dominant type of meaning duality causing humor. This study also found that one meme can contain two ambiguities. Among the five types of ambiguity, this study found a different characteristic of humor for pragmatic ambiguity. These findings can help unveil how humans play with English to create humor.